2022
DOI: 10.3389/fpubh.2022.801109
|View full text |Cite
|
Sign up to set email alerts
|

Ambulophobia as a Specific Phobia—Defining the Problem Among Patients of Long-Term Care Facilities in Poland

Abstract: BackgroundAmbulophobia is a type of specific phobia that involves a fear of walking. This phobia mainly affects older people, who prefer not to leave their bed or home to avoid walking on uneven surfaces and reduce the risk of falling. The problem seems to be very important in terms of public health and the organization of long-term care, as Poland has one of the highest rates of elderly population growth.ObjectivesThe aim of the study was to determine the prevalence of ambulophobia among patients of long-term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…These issues, in terms of neck and back pain, were raised by researchers including Asiri et al [42]. This aspect additionally relates to fear of falling [1] and cancer stage [43,44]. Caraceni and Shkodra [43] indicated that at least half of PLWC experience pain of hard-to-define but severe intensity in various locations of the body, and that its nature excluded them from daily functioning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These issues, in terms of neck and back pain, were raised by researchers including Asiri et al [42]. This aspect additionally relates to fear of falling [1] and cancer stage [43,44]. Caraceni and Shkodra [43] indicated that at least half of PLWC experience pain of hard-to-define but severe intensity in various locations of the body, and that its nature excluded them from daily functioning.…”
Section: Discussionmentioning
confidence: 99%
“…Fear of movement, as contrasted with ambulophobia [1], is known in the scientific literature under the term kinesiophobia and refers to an excessive, irrational and debilitating fear of performing physical movement, resulting from a sense of vulnerability to painful injury or re-injury [2]. Kinesiophobia alters the way people move and causes an adaptation of motor behavior to avoid or control pain, providing a substrate for motor passivity [3].…”
Section: Introductionmentioning
confidence: 99%